Russian tourists as wellness service consumers in Peurunka Spa Hotel - Ilina, Aleksandra (2019)
Demand for new services and interest in health and wellbeing nowadays has forced the tourism industry to create new attributes of attraction in order to maintain customer flow at high levels. The situation with the international sanctions (including economic, diplomatic and sports sanctions) against Russia and the collapse of the Russian ruble has made it difficult to attract Russian customers to Finland as their ability to spend money on traveling has decreased significantly. Particularly the Finnish tourism industry has struggled with searching the ways to bring back the same turnovers that it had before the summer of 2014. The aim of this study is to identify the potential wellness customers of Peurunka Spa Hotel among Russian tourists. This is a quantitative research, which uses the data of 75 participants collected through a questionnaire. The data was acquired in 2014 as part of a research project of active and wellness tourism in the rehabilitation and wellness center Peurunka in Central Finland. The study compares attitudes and behaviors of Russian tourists before and after the tremendous changes on the tourism market that affected Finland and lowered the number of tourists from Russia there. The questionnaire includes four parts which each focus on certain aspects related to the case company, to Russian travelers and their expectation and experiences at the Peurunka Spa Hotel. The results of this study illustrate that among the factors that have a great impact in Russian customers is the usage of adequate promotion channels, depending on the age, gender, as well as that a destination referral from a friend or co-worker plays an important and is considered to be a reliable source of information for Russians. Additionally, the study discovered that Russian tourists tend to come back to the same facility if their previous experiences were enjoyable. The results also reveal that tourists who are concerned about their health and who are regularly physically active are more likely to be attracted by the wellness services of a holiday destination. The majority of the Peurunka’s customers belong to the category of family travelers, and therefore, the availability of family packages for all the services has a potential to increase their satisfaction. Most of the tourists from Russia belong to the middle-age category of customers, which means that the focus of services must be rather on wellness than on rehabilitation and medical diagnostics.